On polyphonic construction: An analysis of Ju|'hoan vocal music (Namibia) - Olivier, Emmanuelle (International Library of African Music, 2007)
The Ju|'hoansi people are one of the few contemporary populations in sub-Saharan Africa who use vocal counterpoint, superposition of voices each with divergent melodic movements and rhythmic articulation. However their music remains largely unknown; only a few isolated articles and recordings have been published, some of these drawing from secondary sources. This article aims at bringing to light the procedures used by the Ju|'hoansi in their construction of vocal counterpoint. Beyond the analysis proper, the question is about conception, intention and realisation of polyphony. In other words, how to characterize Ju|'hoan music: by its polyphonic techniques or by the procedures followed to reach the counterpoint? It will become clear that Ju|'hoan counterpoint is not at the root of every song, as is the case with most of other African polyphonic music, but is the result of complex compositional and performing processes.
Keywords: African Music; Namibia